Ultraviolet-Filtering Luminescent Transparent Coatings for High-Performance PTB7-Th:ITIC–Based Organic Solar Cells - Farinhas, Joana; Correia, Sandra F. H.; Fu, Lianshe; Botas, Alexandre M. P.; André, Paulo S.; Ferreira, Rute A. S.; Charas, Ana (Frontiers in Nanotechnology, 2021)
Photovoltaic (PV) devices based on organic heterojunctions have recently achieved remarkable power conversion efficiency (PCE) values. However, photodegradation is often a cause of dramatic drops in device performance. The use of UV-absorbing luminescent downshifting (LDS) layers can be a mitigation strategy to simultaneously filter UV radiation reaching the device and re-emit it with lower energy, in the visible spectral range, matching the maximum spectral response of the PV cells and thus enabling to increase the photocurrent generated by the cell. In this work, we report the use of a Eu3+-doped siliceous-based organic-inorganic hybrid as a coating on organic solar cells based on the PTB7-Th: ITIC bulk heterojunction with the purpose of increasing their performance. We found that the applied coatings yield a PCE enhancement of ~22% (from 3.1% to 3.8%) in solar cells with spin-coated layers, compared with the bare solar cells, which is among the highest performance enhancements induced by plastic luminescent coatings.